Romanticism in the Works of Ted Hughes: Exploring the Fusion of Emotive Sensibility and Imagination in Ted Hughes' Works (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Romanticism, controversial since its beginning is now a clearly marked vision. Modern scholars- W.K. Wimsatt (1947), M.H. Abrams (1957), Frank Kermode (1957), R.A. Foakes (1958), Rene Wellek and Northrop Frye (1963) have almost resolved the confusion regarding the philosophy of Romanticism with the result that it comes out as the vision comprising of the fusion of the emotive sensibility and the imagination.